Transnationalism of Nusantara ʻUlamāʻ Scholarly Knowledge: Intellectual Networks and the Circulation of Islamic Knowledge in Global History of the 18th–20th Centuries - Ananda Bagus Pradita; Ahyaul Ahnafia Sholeha; Muhammad Noor Sulaiman Syah (Yayasan Albahriah Jamiah Indonesia, 2026)
Studies on the Jawi ʻulamāʻ network have developed extensively, although some strands of global Islamic historiography still treat the Nusantara archipelago as a peripheral space in the formation and circulation of Islamic knowledge. The limitations of previous studies are evident in the minimal explanation of the position of Nusantara ʻulamāʻ as interregional liaisons and their role in shaping the flow of knowledge across Islamic regions from the 18th to the early 20th centuries. This study aims to reconstruct the structure of the Nusantara ʻulamāʻ intellectual network and explain the mechanisms of Islamic knowledge circulation that connect the Malay world with centers of Islamic scholarship. This study uses qualitative methods and a transnational intellectual history approach, employing an intellectual network analysis of ʻulamāʻ works, scientific chains of transmission, intellectual biographies, and global Islamic historical literature. The results show a multidirectional network pattern, characterized by the mobility of ʻulamāʻ to Mecca, Medina, Cairo, and Hadramawt, as well as the formation of scholarly communities that bring together actors from various regions. The scientific chains of transmission function as an instrument of legitimacy, a medium of intellectual integration, and a means of distributing religious authority. The production of books, sharḥ, ḥashiyah, and treatises demonstrates the involvement of Nusantara ʻulamāʻ in the reproduction, adaptation, and development of Islamic discourse. The development of printing and educational networks accelerated the circulation of ideas across the Malay world and other Islamic regions. These findings demonstrate the position of Nusantara ʻulamāʻ as active nodes in the global network of Islamic knowledge, thus requiring a reading that positions Nusantara as a center for the articulation and transmission of knowledge across regions.